Złożoność oprogramowania - interpretacje pojęcia - Kobyliński, Andrzej; Chodoła, Tomasz (Software complexity - interpretation of the notion, 2006)
There are four aspects of software production that are inherently difficult: complexity, conformity, changeability and invisibility. In the paper the concept of “complexity” is thoroughly analyzed. The paper provides a short overview of different approaches to software complexity: psychological, code, semantic, syntactic, computational, algorithmic, problem, organizational, process, entropie, software science, function points, graph, cyclomatic, essential, data, fan and style complexity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 23-31